2013
DOI: 10.1167/iovs.12-11301
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Progression in Glaucoma Suspects With Longitudinal Estimates of Retinal Ganglion Cell Counts

Abstract: PURPOSE. We evaluated the ability of baseline and longitudinal estimates of retinal ganglion cell (RGC) counts in predicting progression in eyes suspected of having glaucoma.METHODS. The study included 288 glaucoma suspect eyes of 288 patients followed for an average of 3.8 6 1.0 years. Participants had normal standard automated perimetry (SAP) at baseline. Retinal nerve fiber layer thickness assessment was performed with optical coherence tomography (OCT). Progression was defined as development of repeatable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…The increasing trend in diagnosed OAG incidence might be related to the ubiquity of advanced diagnostic tools (eg, optical coherence tomography), physician awareness, the high prevalence of myopia, and the accessibility of health care in Taiwan. 3,9,10,[18][19][20] Optical coherence tomography provides for the analysis of retinal nerve fiber layer and retinal ganglion cells, allowing ophthalmologists to diagnose ocular diseases early. 18,20 Moreover, myopia is a risk factor for OAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing trend in diagnosed OAG incidence might be related to the ubiquity of advanced diagnostic tools (eg, optical coherence tomography), physician awareness, the high prevalence of myopia, and the accessibility of health care in Taiwan. 3,9,10,[18][19][20] Optical coherence tomography provides for the analysis of retinal nerve fiber layer and retinal ganglion cells, allowing ophthalmologists to diagnose ocular diseases early. 18,20 Moreover, myopia is a risk factor for OAG.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,10,[18][19][20] Optical coherence tomography provides for the analysis of retinal nerve fiber layer and retinal ganglion cells, allowing ophthalmologists to diagnose ocular diseases early. 18,20 Moreover, myopia is a risk factor for OAG. 3,21 According to the Taiwan National Health Interview Survey, the overall prevalence of myopia in Taiwan was 46.7% in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, changes in neuroretinal rim area, as measured by CSLO, were shown to predict future visual field losses 35–40. More recently, longitudinal studies using spectral domain OCT have shown that changes in RNFL thickness were also highly predictive of future functional losses in glaucoma suspects 41 42. However, in order to show that structural measurements can be used as reliable surrogate endpoints, one has to also demonstrate that the effect of treatment on changes in structure is a reliable predictor of the effect of treatment on changes in function.…”
Section: Reviewmentioning
confidence: 99%
“…In order to assess the utility of RGC counts in predicting progression, Meira-Freitas and colleagues 27 followed 288 eyes of 288 patients suspected of having glaucoma for a total of 3.8 ± 1.0 years. Of the 48 eyes that showed progression during the follow-up period, the mean rate of change in estimated RGC counts was −18,987 cells/y in progressors and −8808 cells/y in nonprogressors ( P < 0.001).…”
Section: Structure and Functionmentioning
confidence: 99%
“…In addition, the longitudinal model including estimates of RGC counts performed significantly better than models including only structural or functional indexes. 27 …”
Section: Structure and Functionmentioning
confidence: 99%